2017
DOI: 10.2139/ssrn.2956238
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Property and Product Market Competition Regulations in a Model with Two R&D Performing Sectors

Abstract: I analyze the impact of intellectual property and product market competition regulations on innovation and long-run growth in an endogenous growth model with two R&D performing sectors. I show that strengthening intellectual property rights and competition in a sector increases its R&D investments. However, these policies adversely affect R&D investments of the other sector. The overall impact of such policies on economic growth is ambiguous because of this. I perform a numerical exercise in an attempt of reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Neves et al (2021) conducted a literature review and meta‐analysis of the link of IPRs, innovation and economic growth, and found that IPRs have an overall positive effect on economic growth. Some scholars believed that intellectual property does not directly affect economic growth (Habib et al, 2019) but indirectly promotes economic growth by stimulating R&D investment (Cho et al, 2015; Jerbashian, 2021; Maskus et al, 2019). For example, Maskus et al (2019) found that stronger patent rights increase R&D intensities in patent‐intensive industries, and patent protection raises R&D in high‐patent industries where countries have more limited equity and credit markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Neves et al (2021) conducted a literature review and meta‐analysis of the link of IPRs, innovation and economic growth, and found that IPRs have an overall positive effect on economic growth. Some scholars believed that intellectual property does not directly affect economic growth (Habib et al, 2019) but indirectly promotes economic growth by stimulating R&D investment (Cho et al, 2015; Jerbashian, 2021; Maskus et al, 2019). For example, Maskus et al (2019) found that stronger patent rights increase R&D intensities in patent‐intensive industries, and patent protection raises R&D in high‐patent industries where countries have more limited equity and credit markets.…”
Section: Literature Reviewmentioning
confidence: 99%